The Effect of Colchicine on St. Thomas II Cardioplegia on Ischemia-Reperfusion Injury: A Histomorphological Study in Rabbits - Rizky Aditya Fardhani; Pribadi Wiranda Busro; Sugisman Sugisman (Lembaga Pengembangan Kinerja Dosen, 2026)
The maternal mortality rate in South Sumatra Province was recorded at 128 cases in 2020 and increased Cardioplegia is an important method for protecting the heart from ischemia-reperfusion (I/R) injury. However, myocardial damage from reperfusion can't be completely prevented by standard cardioplegia solutions alone. The St. Thomas II cardioplegia solution, with a lower potassium concentration, has been shown to have a cardioprotective effect, while colchicine, as an anti-inflammatory agent, works by inhibiting NLRP3 inflammasome activation and neutrophil modulation. This experimental study used a randomized controlled trial (RCT) post-test-only design on 12 New Zealand white rabbits, which were randomly divided into two groups: a control group (St. Thomas II) and a treatment group (St. Thomas II + colchicine). The primary outcome was the degree of myocardial histomorphological damage at 200× magnification. The results showed that five out of six samples from the control group had severe damage (score 3), while five out of six samples from the treatment group had no damage (score 0). A Mann-Whitney test yielded a p-value of 0.0152, indicating a significant difference. The addition of colchicine to St. Thomas II was shown to significantly reduce myocardial histomorphological damage. These findings suggest that colchicine could be considered as a cardioplegia adjuvant to enhance myocardial protection during cardiac surgery.